Increasing The Value of Budget Performance Based on Output Achievement, Absorption, Efficiency, And Consistency of Budget Absorption with Plans - Sulistyorini; Sariri, Fatimah; Septiana, Dinda Herli (Proceeding of International Joint Conference on UNESA, 2024)
UNESA's budget management as a PTN BH must not only be good at the internal level, but must also be good and able to compete at the external level, must be able to compete with 20 other PTN BH. This research is very important and strategic to support UNESA to have a very good NKA. Therefore, this research aims to (1) Analyze output achievement in budget management at FMIPA UNESA; (2) Analyze budget absorption in budget management at FMIPA UNESA; (3) Analyze efficiency in budget management at FMIPA UNESA; and (4) Analyze the consistency of budget absorption against planning in budget management at FMIPA UNESA. This research uses a qualitative and descriptive approach, using two types of data, and named primary data and secondary data. Primary data is expected to be presented on the form of tables or diagrams, analyzed by making interpretations and theoretically, and comparing with other studies. While secondary data uses documentation techniques, namely by utilizing financial data and other data that already exist in FMIPA. This research is expected to produce outputs in addition to research reports also presented in national seminars or scientific papers in the form of articles published in national or international journals.